THE EFFECT OF FORMATIVE ASSESSMENT OF PROGRAMMED DAILY ASSESSMENT ON LEARNING MOTIVATION AND ITS IMPACT ON STUDENTS' ACADEMIC ACHIEVEMENT - Sukowati, Berliani Ardelia; Nisita, Indriastri; Sukimin, Sukimin; Setyaningsih, Nining (Universitas Tanjungpura, 2025)
Programmed Daily Assessment is an assessment that is scheduled systematically and programmatically by schools with provisions for time, form, and frequency that are adjusted for all teachers. The purpose of this study was to examine the direct effect of programmed daily assessment on learning motivation, examine the direct effect of programmed daily assessment and learning motivation on learning achievement, and examine the indirect effect of programmed daily assessment on learning achievement through learning motivation. This research method is quantitative with a correlational design. The research subjects were 82 8th-grade students at one of the junior high schools in Karanganyar Regency. Data collection techniques used questionnaires to measure learning motivation and math tests for learning achievement. The data were analyzed using path analysis with the SPSS version 25 program which was preceded by prerequisite analysis tests (normality, linearity, multicollinearity, heteroscedasticity). The results of the study show that programmed daily assessment has no direct effect on students